ERROR ANALYSIS OF COUNTABLE AND UNCOUNTABLE NOUNS ON PROCEDURE TEXT WRITING AT THE TENTH GRADE STUDENTS OF SMAS HKBP SIDORAME MEDAN - Yesica Hageltira Sitorus; Usman Sidabutar; Neni Triana Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In this study, the problem encountered was the incorrect use of countable and uncountable nouns in procedural texts written by 10th-grade students at SMAS HKBP Sidorame Medan. Students often had difficulty distinguishing between these two types of nouns, especially in using quantifiers and forming plurals. The purpose of this study was to identify the types of errors made by students and determine which errors occurred most frequently. This study referred to the Error Analysis theory proposed by (Dulay, H., Burt, M. and Krashen, 2013). The errors were classified into four categories: omission, addition, misformation, and misordering. The research used a qualitative descriptive approach. Data were collected from students’ procedural texts and analyzed based on the error classification. The results showed that out of 100 identified errors, misformation was the most frequent error, accounting for 37%. This was followed by addition errors (29%), omission (21%), and misordering (13%). In addition, errors in using uncountable nouns were higher (70%) than countable nouns (30%). These findings indicate that students still face difficulties in understanding and applying the rules of countable and uncountable nouns. The dominance of misformation errors shows that students do not fully understand noun forms in English grammar. Therefore, teaching countable and uncountable nouns needs more attention and a structured approach to improve students’ grammatical accuracy in writing.